Timing Matters: Exploring the Role of the Time to Onset in Recall Bias for Adverse Events Following Immunization (AEFIs) of COVID-19 Vaccines from Spontaneous Reports - Joep Scholl; Florence van Hunsel; Eugene van Puijenbroek (Pharmacoepidemiology)
Objective: The aim of this study was to investigate a possible relationship between the time to onset (TTO) of adverse events following immunization (AEFIs) and recall bias and to compare it between AEFIs of COVID-19 vaccines reported though the spontaneous reporting system (SRS) and those from a cohort event monitoring (CEM) study. Methods: A retrospective study comparing TTO patterns of AEFIs of four COVID-19 vaccines from the SRS and those from a CEM study was performed. Reports concerning AEFIs related to COVID-19 vaccination were used for the study. TTO patterns were stratified for vaccination dose number, perceived burden of the AEFI, and for being pre-defined. Additionally, since menstrual disorders received much media attention, their effect on the TTO pattern was investigated for SRS reports only. Results: A total of 160,613 reports from the SRS and 19,979 from the CEM, containing 755,647 and 103,703 AEFIs, respectively, were included. For AEFIs with a short TTO, no differences in TTO patterns were observed. However, the median TTO for AEFIs from the SRS was lower with increasing TTO duration. There were differences in both median TTO and time to reporting for AEFIs reported before and during episodes of media attention, but no correlation between the two could be found. Conclusions: Based on the performed TTO analyses, recall bias does not seem to be more evident in SRS compared to CEM studies for AEFIs with a short TTO. For AEFIs with a longer TTO, this may be more pronounced.